2014
DOI: 10.1089/jop.2013.0238
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of β Receptor Blockade Through Propranolol on Corneal Neovascularization

Abstract: Topical propranolol 1 or 0.5 mg/mL does not have a significant inhibitory effect on alkali-induced corneal NV in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…[17] Simavli et al in 2014 have shown topical propranolol has no significant inhibitory effect on CNV statistically. [10] While our study shows topical propranolol can inhibit CNV statistically.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…[17] Simavli et al in 2014 have shown topical propranolol has no significant inhibitory effect on CNV statistically. [10] While our study shows topical propranolol can inhibit CNV statistically.…”
Section: Discussionmentioning
confidence: 58%
“…The concentrations of topical Propranolol were chosen from previous studies. [10,12] All treated and control eyes were photographed using a chargecoupled device camera attached to a slit-lamp biomicroscope at ×40 magnification. Photographs were obtained before drug administration and at 1 and 2 weeks after therapy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A first study observed that propranolol eye drops 0.1 and 0.05%, administered twice a day for 7 days, was not able to reduce alkali-induced corneal neovascularization in rats. [ 21 ] On the contrary, topical timolol 0.5% twice per day significantly reduced the area of neovascularization induced by silk sutures in rabbits, [ 22 ] and similar results were obtained with 1% propranolol eye drops, 3 times a day for 2 weeks, starting immediately after suture removal. [ 23 ] A more recent study, performed in mice subjected to corneal sutures, showed that 6 subconjunctival injection of 0.5% timolol significantly reduced the corneal neovascularization, the inflammatory infiltration, and the expression of VEGF, TNFα and IL-6.…”
Section: Discussionmentioning
confidence: 69%